First estimates of the fundamental parameters of the very small open cluster Ruprecht 1 - Piatti, Andres Eduardo (2008)
New CCD observations with the Washington C and T1 filters in the field of the open cluster Ruprecht 1 are presented. The cluster turned out to be very small, its linear radius being 2.6 ± 0.2 pc. Ruprecht 1 is moderately reddened [E(B-V) = 0.25] and moderately young (∼ 230 Myr). Heliocentric distances of 1.9 ± 0.4 kpc and 1.5 ± 0.3 kpc are determined for Z (metallicity) = 0.02 and 0.008, respectively, although evidence is presented favouring a solar metal content rather than a subsolar one. We compare the cluster properties with those of known open clusters located within 1 kpc around it.